Aplikacja wielowymiarowych modeli ARIMA w pakiecie SCA - Chodakowska, Ewa (An Application of Multivariate ARIMA Models in SCA Statistical System, 2005)
MARIMA models can be used in a variety of applications. This class of models effectively connects the basic concepts of the regression model with these of ARIMA models. However, they are not frequently used in practice, because popular computer software for statistical data analysis does not include algorithms for MARIMA models identification and estimation. SCA Statistical System is one of the few systems that supports MARIMA method of forecasting. In this paper methology of MARIMA models' construction in SCA has been presented. On the is of a time series analysis consecutive phases of model-building process have n described and discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 349-357